The Single-Photon Model of Search of Pulse Signals for Telecommunication Systems - Y. Rumyantsev, K; A. Albogachieva, L; D. Linenko, P (International Journal of Engineering and Technology, 2018)
Detection of the optical pulse reception moment is a necessary condition for communication between moving correspondents. The search algorithm of pulse signals in a photons registration mode (single-photon pulses) is known. It is considered that in a reception complex the optical signals period is known. The photoreception channel consists of an single-photon dissector, the electron amplifier, and the amplitude discriminator. In the time frame which is equal to the optic pulse-repetition period, the moment of amplitude discrimination level equality fixed. The analysis of the threshold reason excess is made in a following frame. At repeated excess of a threshold it is considered, that useful radiation is revealed. Otherwise the decision on absence of a source radiation is passed. The system passes to the review of a new spatial element of decomposing in supervised spaces. At the second excess of a threshold it is considered, that useful radiation is revealed. Otherwise the system passes to the review of a new spatial element of decomposing in controllable space. The model is developed for check of algorithm efficiency, measurement of statistical characteristics of search system of radiation sources with detection of the reception moment of optical pulse. In system the single-photon dissector with the limited pass-band is used. By means of the developed simulation model working capacity is proved and algorithm efficiency is checked up, statistical characteristics of search system of radiation sources with detection of the occurrence moment of a signal are measured at use of an single-photon dissector with the limited pass-band.Â Â